2021
DOI: 10.1016/j.ekir.2020.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cytokine Profiling to Predict Steroid Resistance in Pediatric Nephrotic Syndrome

Abstract: Introduction Glucocorticoids (GCs) are the primary treatment for nephrotic syndrome (NS), although ∼10% to 20% of children develop steroid-resistant NS (SRNS). Unfortunately, there are no validated biomarkers able to predict SRNS at initial disease presentation. We hypothesized that a plasma cytokine panel could predict SRNS at disease presentation, and identify potential pathways regulating SRNS pathogenesis. Methods Paired plasma samples were collected from 26 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…Our study has female predominance about 54% and that is in agreement with Agrawal et al, [10] study in which his study group has also female predominance that represent 55%. Our study showed no significant difference was found between patients & control group regarding blood pressure.…”
Section: Discussionsupporting
confidence: 93%
“…Our study has female predominance about 54% and that is in agreement with Agrawal et al, [10] study in which his study group has also female predominance that represent 55%. Our study showed no significant difference was found between patients & control group regarding blood pressure.…”
Section: Discussionsupporting
confidence: 93%
“…In another study, Khatibi et al, [18] showed a higher level of uMCP-1 in SRNS patients compared to SSNS patients, indicating that uMCP-1 can predict glucocorticoid resistance. In addition, our findings were consistent with those of Agrawal et al, [19] who found that uMCP-1 may distinguish children with SRNS from those with SSNS at the time of initial disease presentation. Moreover, Angela [16] noted that patients with SRNS higher concentrations of MCP-1 in the urine compared to SSNS patients (p < 0.001).…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have shown that cytokines are closely related to the pathogenesis of nephropathy [22][23][24]. In many nephropathy-related studies [25][26][27], the expression or concentration levels of serum IFN cytokines presented conflicting results. TNF levels were agreed to be significantly elevated.…”
Section: Discussionmentioning
confidence: 99%